Assessing the Experiences of IUD Users Along the Thailand-Burma Border - Gedeon, Jillian (Université d'Ottawa / University of Ottawa, 2014)
The forced displacement of over 100 ethnic minorities in Burma over the last few decades has negatively impacted the overall health of this population. The maternal mortality ratio along the Thailand-Burma border is one of the highest in the world and access to life saving reproductive health services and technologies is minimal. The purpose of this study is to understand the experiences of intra-uterine device (IUD) users living along the border while exploring the various influences that have shaped women’s reproductive experiences. Using qualitative methods, I found that differences in legal/minority status, culture, availability of services, health status, financial status, and education/awareness of family planning can determine women’s overall health in the region. The use of the IUD helped reduce the influence of these factors and provided women with reproductive autonomy; the contraceptive technology was greatly appreciated by users for its efficiency, its effectiveness, and its safety. The findings from this study suggest that the IUD can address significant reproductive health problems in the region and should be made more widely available along the Thailand-Burma border.
Keywords: Interdisciplinary School of health Sciences; Qualitative; Women's health; Thailand-Burma